Refuse-derived fuel(RDF) production and analysis in mechanicalbiological treatment (MBT) plant from the municipal solid waste - Ahmed, Nawzad Noori (Sulaimani Journal for Pure and Applied Sciences, 2023)
This study reports on the potential of refuse-derived fuels (RDF), which are produced from Sulaimani Municipal solid waste (MSW) using a biodrying process. Plastic, organic wastes, iron materials, and textiles were used in the formulation of RDF samples. A sample of raw MSW material was collected comprising of 40.6% organic, 29.3% plastic, 6.3% Textiles, 5.1% paper, 3.1% wood, 4.6% glass and stone, 5.2% iron containing materials, and 1.3% others. Physical and chemical properties of the RDF were investigated, including its moisture, ash, total chlorine, and heavy metal content with, calorific value. Based on the experimental results, RDF produced from MSW can be classified into net calorific and total chlorine content values NCV 2 and Cl 4 respectively. In accordance with the European Committee for Standardization (CEN standard), the results of this preliminary investigation of RDF samples made from non-biodegradable and non-recyclable MSW fractions, is necessary to analyze a larger pool of samples in order to project appropriate RDF energy-recovery-enhancing composition.
Keywords: Rheumatoid RDF; Calorific value; Heavymetal; Wastetoenergy